CLINICAL EFFECTIVENESS OF DIAPEUTIC, ENDOSCOPIC, AND X-RAY SURGICAL METHODS IN THE TREATMENT OF GALLSTONE DISEASE COMPLICATIONS. - Shomurodov Khabibullo Abdumalik ugli (The latest pedagogical and psychological innovations in education, 2025)
Biliary peritonitis is a serious complication of acute cholecystitis. At the same time,..."despite the seriousness of this problem, little attention is paid to biliary peritonitis, although the mortality rate in this complication, according to various authors, ranges from 6.2 to 24%" .